Thyroid sequestration and Hashimoto - Rodríguez, José Luis; Palacio, José Luis; Maedo, Noemí; Chiossoni, Marta; Bergalli, Luis; Navarrete, Héctor D (Cirugía del Uruguay, 1992)
The author presents an infrequent entity such as a sequestered thyroid nodule, defines it, makes a brief bibliographical revision, emphasizing aspects of the differential diagnosis with other entities which it can be confused with, and comes to the conc/usion that its importance /ies in the fact that confusion due to ignorance can lead to serious diagnostica/ and therapeutica/ errors